An Aortic Pseudoaneurysm following Bentall Procedure - Koza, Yavuzer; Kaya, Uğur; Tas, Muhammed Hakan; Simsek, Ziya (AORTA, 2014)
We describe a rare case of an ascending aortic pseudoaneurysm detected incidentally at coronary angiography in a 64-year-old man with a history of a Bentall procedure 8 years previously. The patient underwent reoperation, with longitudinal opening and cleaning of the aortic pseudoaneurysm and graft repair of the defect. This report highlights the insidious late onset of pseudoaneurysm and the importance of its detection and treatment.
Keywords: Aortic pseudoaneurysm; Bentall procedure